Tourism as a Driver of the Local Economy: Analysis of the Impact of Mutiara Beach Development on the Livelihoods of Gumanano Village Community, Central Buton Regency - Nesha Rizky Ashari; Abdullah Abdullah (Jurnal Manajemen dan Inovasi Pariwisata, 2026)
Tourism as a Driver of the Local Economy: Analysis of the Impact of Mutiara Beach Development on the Livelihoods of Gumanano Village Community, Central Buton Regency. This study aims to analyze the economic impact of Mutiara Beach tourism development on the livelihoods of local communities in Gumanano Village, Mawasangka District, Central Buton Regency. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, field observations, and documentation, with informants selected via purposive sampling. Data analysis followed the interactive model of Miles and Huberman, with validity ensured through source, technique, and time triangulation. The findings indicate that the tourism sector positively influences community livelihoods through increased income, employment creation, and micro, small, and medium enteNrprise (MSME) growth. Based on the Sustainable Livelihood Framework, tourism has strengthened communities’ financial, social, human, and physical capital. An economic multiplier effect from tourism activities was also identified. Nevertheless, challenges remain, including limited business capital, suboptimal destination promotion, and the risk of economic dependency. The study recommends community-based tourism management oriented toward sustainable empowerment to ensure equitable distribution of economic benefits.